Using the Information Systems Success Model to Predict Factors Affecting Intention to Adopt Blended Learning in Physical Education - Jing Fu,; Songyu Jiang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study investigates the various factors that influence the intention to adopt blended learning in physical education (BLPE) by utilising the Information Systems Success Model (ISSM). The participants consist of first-year undergraduate students who are pursuing a degree in physical education in China. A convenient sampling method gathered information from 374 individuals. In addition, the study investigated the correlation between the quality of information, system quality, attitude, and intention to adopt blended learning in physical education through the use of the Structural Equation Model (SEM). The results indicate a strong correlation between the quality of information, the quality of the system, and the attitude and intention towards the use of blended learning in physical education. Furthermore, attitude has a positive correlation with the intention to use BLPE. In addition, the model places significant emphasis on attitude as a crucial mediator. The findings suggest that incorporating blended learning models has the potential to improve student engagement and enhance learning outcomes in the field of physical education. The findings provide valuable insights for educators, administrators, and policymakers who are exploring blended learning models in physical education.